2020
DOI: 10.1007/s10709-020-00085-4
|View full text |Cite
|
Sign up to set email alerts
|

A computational genome-wide analysis of long terminal repeats retrotransposon expression in sunflower roots (Helianthus annuus L.)

Abstract: GeneticaA computational genome-wide analysis of long terminal repeats retrotransposon expression in sunflower roots (Helianthus annuus L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…The low transcript abundance of LTR-REs in plants has often been reported [51,[53][54][55][56]. In certain species, increased expression in plants exposed to biotic or abiotic stresses was reported; however, the global level of expression remained low even during stressful treatments [57][58][59][60][61][62]. Our data indicated that 21/180 sequences were barely expressed and only three sequences were transcribed at levels comparable to those of the majority of actin-and tubulin-encoding reference genes.…”
Section: Discussionsupporting
confidence: 56%
“…The low transcript abundance of LTR-REs in plants has often been reported [51,[53][54][55][56]. In certain species, increased expression in plants exposed to biotic or abiotic stresses was reported; however, the global level of expression remained low even during stressful treatments [57][58][59][60][61][62]. Our data indicated that 21/180 sequences were barely expressed and only three sequences were transcribed at levels comparable to those of the majority of actin-and tubulin-encoding reference genes.…”
Section: Discussionsupporting
confidence: 56%
“…Generally, the mobilization of a TE occurs when the organism is subject to conditions of genomic stress such as biotic or abiotic stresses, polyploidy and interspecific hybridizations typical in plants but not completely absent in animals (Bourque et al, 2018;Casacuberta & González, 2013;Dubin, Mittelsten Scheid, & Becker, 2018;Mascagni et al, 2020;Zhao et al, 2018).…”
Section: It Would Take 30 Years Before the Molecular Structures Of Acmentioning
confidence: 99%
“…Generally, the mobilization of a TE occurs when the organism is subject to conditions of genomic stress such as biotic or abiotic stresses, polyploidy and interspecific hybridizations typical in plants but not completely absent in animals (Bourque et al, 2018; Casacuberta & González, 2013; Dubin, Mittelsten Scheid, & Becker, 2018; Mascagni et al, 2020; Usai et al, 2020; Vangelisti, Mascagni, Giordani, et al, 2019; Vangelisti, Mascagni, Usai, et al, 2019; Vangelisti, Usai, et al, 2019, 2020; Zhao et al, 2018). Given also the irregularity in the course of evolution, with periods of rapid change alternated to long periods of stability, it is likely that in some cases the TEs have expanded within the genomes as predicted by the theory of punctuated equilibria (Eldredge & Gould, 1972).…”
Section: The Discovery Of the Tesmentioning
confidence: 99%
“…Although transposon-silencing mechanisms have largely been deciphered, it is unclear how some transposons are expressed when silencing system is on. Here, we applied an integrated approach to elucidate genomic and transcriptomic features as well as the mobilome activities of expressed RTEs of sunflower, a species for which retrotransposon expression has been demonstrated [26][27][28][29][30][31]. We observed 44 expressed LTR retrotransposons in the sunflower genome and studied their genomic and transcriptomic features and transposition activity.…”
Section: Tens Of Rtes With Distinct Features Are Expressed In Plant Smentioning
confidence: 99%
“…In this study, we aimed to depict the distinct genomic and transcriptomic features and to obtain insight into the mobilome (transposition) activity of expressed RTEs. For this, we exploited sunflower (Helianthus annuus), a species with a big genome (~3 Gb), and for which RTE transcription has been shown in several previous studies [26][27][28][29][30][31]. Previous reports on RTE transcription in sunflower focused on distinct TE elements isolated from BAC clones, or those assembled by short-read clustering; they did not include genome-based characterization of expressed RTEs (exRTEs) and their transcripts.…”
Section: Introductionmentioning
confidence: 99%